Characteristics of the case mix, organisation and delivery in cancer palliative care: a challenge for good-quality research. Issue 4 (31st May 2016) - Hjermstad, M J; Aass, N; Aielli, F; Bennett, M; Brunelli, C; Caraceni, A; Cavanna, L; Fassbender, K; Feio, M; Haugen, D F; Jakobsen, G; Laird, B; et al.
Abstract : Objectives: Palliative care (PC) services and patients differ across countries. Data on PC delivery paired with medical and self-reported data are seldom reported. Aims were to describe (1) PC organisation and services in participating centres and (2) characteristics of patients in PC programmes. Methods: This was an international prospective multicentre study with a single web-based survey on PC organisation, services and academics and patients' self-reported symptoms collected at baseline and monthly thereafter, with concurrent registrations of medical data by healthcare providers. Participants were patients ≥18 enrolled in a PC programme. Results: 30 centres in 12 countries participated; 24 hospitals, 4 hospices, 1 nursing home, 1 home-care service. 22 centres (73%) had PC in-house teams and inpatient and outpatient services. 20 centres (67%) had integral chemotherapy/radiotherapy services, and most (28/30) had access to general medical or oncology inpatient units. Physicians or nurses were present 24 hours/7 days in 50% and 60% of centres, respectively. 50 centres (50%) had professorships, and 12 centres (40%) had full-time/part-time research staff. Data were available on 1698 patients: 50% females; median age 66 (range 21–97); median Karnofsky score 70 (10–100); 1409 patients (83%) had metastatic/disseminated disease; tiredness and pain in the past 24 hours were most prominent. During follow-up, 1060 patients (62%) died; 450 (44%) <3 months from inclusion and 701 (68%) within 6 months. ANOVA and χ 2 tests showed that hospice/nursing home patients were significantly older, had poorer performance status and had shorter survival compared with hospital-patients (p<.0.001). Conclusions: There is a wide variation in PC services and patients across Europe. Detailed characterisation is the first step in improving PC services and research. Trial registration number: ClinicalTrials.gov Identifier: NCT01362816 .